Handling of Common Laboratory Animals in Biomedical Study - Rachmat Hidayat; Patricia Wulandari (HM Publisher, 2021)
Mice are usually caught and lifted by the tail. The tail should be grasped abouttwo-thirds of the way down. With this simple method of holding, they may betransferred to another cage or a balance, identified or sexed; but such restraint isnot sufficient for treatment and close examination. For more effective control, themouse may be held by the tail and placed on a table or other surface, preferablyone that the mouse can grasp, and the loose skin over the neck and shouldersgrasped with thumb and fingers.